Bio-Physiological Indicators in Evaluating Archery Performance - Rabiu Muazu, Musa; Zahari, Taha; Anwar, P. P. Abdul Majeed; Mohamad Razali, Abdullah (Springer, 2019)
The present chapter measured the association of archery performance in relation to bio-physiological indicators, namely calories intake, resting respiration, heart rate, systolic as well as diastolic blood. It was established from the investigation that a high calorie intake, resting respiratory rate and a lower level of heart rate in conjunction with lower blood pressure are positively linked with a higher archery shooting score. Moreover, it is shown from the present investigation that the LR model could provide a good prediction of LPA and HPA based on the performance indicators examined.